Comparison of staging MRI to re‐resection for localised bladder cancer: Narrative review - Hugo Klempfner; Paul Anderson (BJUI Compass)
Abstract Introduction Bladder cancer (BCa) is characterised by high prevalence, multifocality, and frequent recurrence, imposing significant clinical and economic burdens. Accurate staging, particularly distinguishing non‐muscle‐invasive bladder cancer (NMIBC) from muscle‐invasive bladder cancer (MIBC) disease, is crucial for guiding treatment decisions. This narrative review explores the potential implications of incorporating multiparametric magnetic resonance imaging (mpMRI) and the Vesical Imaging Reporting Data System (VI‐RADS) into BCa staging, focusing on repeat transurethral resection of bladder tumour (re‐TURBT). Methods A comprehensive search of PubMed, EMBASE, and MEDLINE databases identified studies published from 2018 to 2023 discussing mpMRI or VI‐RADS in the context of re‐TURBT for BCa staging. Studies meeting inclusion criteria underwent qualitative analysis. Results Six recent studies met inclusion criteria. VI‐RADS scoring, accurately predicted muscle invasion, aiding in NMIBC/MIBC differentiation. VI‐RADS scores of ≥3 indicated MIBC with high sensitivity and specificity. VI‐RADS potentially identified patients benefiting from re‐TURBT and those for whom it could be safely omitted. Discussion mpMRI and VI‐RADS offer promising prospects for BCa staging, potentially correlating more closely with re‐TURBT and radical cystectomy histopathology than initial TURBT. However, validation and careful evaluation of clinical integration are needed. Future research should refine patient selection and optimise mpMRI's role in BCa management. Conclusion VI‐RADS scoring could revolutionise BCa staging, especially regarding re‐TURBT. There is potential that VI‐RADS correlates more with the histopathology of re‐TURBT and radical cystectomy than initial TURBT. While promising, ongoing research is essential to validate utility, refine selection criteria, and address economic considerations. Integration of VI‐RADS into BCa staging holds potential benefits for patients and health care systems.